Islam dan HAM: Tarik Menarik antara Absolutisme dan Relativisme - Roibin, Roibin (UIN Maulana Malik Ibrahim Malang, 2000)
A careful examination of the human rights portrait that develops in the reality of macro society, it seems that the theme can not be separated from the theoretical scientists who are considered to still have relevance. Human rights concepts emerging from individuals will always contradict the offer of human rights concepts born from institutions, ranging from micro to macro (state institutions). Because in practice the tendency of the concept of human rights will always be closely related to the interests of the ruler of each of the human rights concept creators. Human rights in Islam have never been suspected as a historical product arising from ideological thought, but it has a theological dimension. Of course in the future all will be accountable before the Divine. In kasamya human rights in the view of Islam is not as a result of political development, but human rights that are transcendently transcribed for the benefit of humans through the Islamic Shariah derived through His revelation. Where is this all encouraged by a belief to raise the dignity of humanity as a noble creature. Mengamati secara cermat potret HAM yang berkembang dalam realitas masyarakat makro, nampaknya tema tersebut belum bisa lepas dari teoriteori ilmuan yang dianggap masih memiliki relevansi. Konsep HAM yang muncul dari individu akan selalu berseberangan dengan tawaran konsep HAM yang lahir dari institusi, mulai dari yang mikro hingga yang makro (institusi kenegaraan). Karena dalam prakteknya kecenderungan konsep HAM akan selalu berkaitan erat dengan kepentingan penguasa dari masing-masing pembuat konsep HAM tersebut. HAM dalam Islam tidak pemah diduga sebagai produk historik yang muncul dari pemikiran ideologis, melainkan ia memiliki dimensi teologis. Tentu kelak ini semua akan dipertanggung jawabkan dihadapan Ilahi. Secara kasamya HAM dalam pandangan Islam bukanlah sebagai akibat dari perkembangan politik, melainkan hak asasi yang tertuang secara transeden untuk kepentingan manusia melalui syariat Islam yang diturunkan lewat wahyu-Nya. Dimana ini semua disemangati oleh satu keyakinan untuk mengangkat harkat kemanusiaan sebagai makhluk yang luhur.